TLR9/MyD88/NF-κB signaling mediates mental stress-induced exacerbation of psoriasis through immune dysregulation in a mouse model - Qiuhe Song; Dongyang Li; Zhihao Yuan; Chaowen Zhang; Jianqiao Wang; Fangfang Liao; Pengfei Xu; Qipeng Xiao (PLoS ONE, 2026)
Objective Psoriasis is a chronic inflammatory autoimmune disease that affects physical and mental health. Mental stress has been shown to exacerbate human psoriasis by unknown mechanism. Methods Peripheral blood mononuclear cells (PBMCs) were collected from patients with psoriasis and mental stress-treated psoriatic mice. The expression levels of TLR9/MyD88/NF-κB pathway-related molecules were analyzed by qRT-PCR and western blotting. Histological examination of skin lesions was examined using hematoxylin-eosin staining. The ratios of Treg/CD4 + T cells and Th17/Treg cells were determined by flow cytometry. The associations among mental stress, the TLR9/MyD88/NF-κB pathway, and psoriasis were explored using pharmacological inhibitors and lentiviral transfection. Results Our findings demonstrated a significant upregulation of TLR9/MyD88/NF-κB pathway-associated molecules in the PBMCs of psoriasis patients, accompanied by elevated expression of inflammatory factors. These observations were validated using a mouse model of psoriasis. Notably, mental stress was shown to activate the TLR9/MyD88/NF-κB pathway and enhance inflammatory factor production, while simultaneously increasing the Th17/Treg ratio and decreasing the Treg/CD4 + T ratio. Therapeutic interventions including antipsychotic sertraline, pathway-specific inhibitors, and lentiviral transfection significantly ameliorated inflammatory markers and improved psoriasis severity grading. Conclusion The results of this study demonstrates that mental stress induces inflammation and immune dysregulation, exacerbating psoriasis progression. These findings provide valuable insights into the pathophysiological mechanisms underlying psoriasis progression, particularly the mental stress-mediated immunoregulatory axis.